Investigation of the Effectiveness of the Combined Treatment of Diabetic Macular Edema - S. I. Zakieva; A. D. Aliyev; A. K. Ahmedov; M. M. Magomedova; M. T. Mikailova (Oftalʹmologiâ)
The purpose: to compare the effectiveness of combination treatment of patients with diabetic macular edema (DMO) and to assess the correlations of clinical, functional and aberrometric indicators.Patients and methods. 47 patients (56 eyes) were examined, 27 were women and 20 were men with DME, the average age was 61.3 ± 1.8 years. The 1st group included 22 patients (27 eyes) who underwent intravitreal administration of the neoangiogenesis inhibitor (IA IN) aflibercept followed by laser retinal coagulation (LRC). The 2nd group included 25 patients (29 eyes) who received a combined surgical intervention, including IA IN aflibercept and one-time subtenon administration of the prolonged corticosteroid betamethasone followed by laser coagulation of the retina. Best corrected visual acuity (BCVA) in the 1st group was 0.51 ± 0.2 digits, in the 2nd group 0.44±0.3 digits. Patients of both groups underwent an average of 5.48 ± 1.5 IVs of IV aflibercept. The observation period was 12 months.Results. According to research data, it was revealed that in the 1st group the BCVA by the end of the treatment period was 0.59 ± 0.22 (р = 0.02), and in the 2nd group this indicator was 0.66 ± 0.25 (p = 0.02). After the 5th injection, there was a statistically significant decrease in CRT by an average of 270.17 ± 92.37 μm in the 2nd group (р = 0.05), and a less significant morphological result was noted in the 1st group (р < 0.05). In both groups, a statistically significant decrease in all components of higher-order aberrations was noted already after the first 3 injections, however, in the 1st group, the result was unstable (p = 0.04).Conclusions. The obtained results indicate that in patients from the 2nd group it was possible to achieve high morphofunctional results and maintain them at a statistically significant level by the end of the observation period in 89% of cases, and in patients of the 1st group in 68% of cases, however, the results turned out to be unstable.